2019
DOI: 10.2967/jnumed.119.229450
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET Dissemination Features in Diffuse Large B-Cell Lymphoma Are Predictive of Outcome

Abstract: We assessed the predictive value of new radiomic features characterizing lesion dissemination in baseline 18 F-FDG PET and tested whether combining them with baseline metabolic tumor volume (MTV) could improve prediction of progression-free survival (PFS) and overall survival (OS) in diffuse large B-cell lymphoma (DLBCL) patients. Methods: From the LNH073B trial (NCT00498043), patients with advancedstage DLCBL and 18 F-FDG PET/CT images available for review were selected. MTV and several radiomic features, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
122
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 26 publications
7
122
1
Order By: Relevance
“…Moreover, Aide et al [ 35 , 40 ] found that skewness of skeletal heterogeneity was a prognostic factor for PFS, and long-zone high gray level emphasis from GLSZM was a prognostic parameter for 2-year event-free survival. Recently, Cottereau et al [ 41 ] reported that the radiomic feature characterizing lesion dissemination was associated with PFS and OS. Our findings are in line with those of studies indicating that the PET-derived radiomic features are useful for patient outcome prognostication in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Aide et al [ 35 , 40 ] found that skewness of skeletal heterogeneity was a prognostic factor for PFS, and long-zone high gray level emphasis from GLSZM was a prognostic parameter for 2-year event-free survival. Recently, Cottereau et al [ 41 ] reported that the radiomic feature characterizing lesion dissemination was associated with PFS and OS. Our findings are in line with those of studies indicating that the PET-derived radiomic features are useful for patient outcome prognostication in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Vercellino and colleagues found high pretreatment MTV to be significantly associated with inferior PFS and OS in this group [75]. Including patients from the LNH073B study, a French working group additionally examined the role of radiomic features characterizing lesion dissemination and reported that combining them with baseline MTV further improves risk stratification in DLBCL patients [76]. However, MTV calculation was carried out rather inconsistently in different working groups, which used both adaptive and fixed thresholds ( Figure 2, Table 2).…”
Section: Recent Advances and Future Directionsmentioning
confidence: 99%
“…These parameters consider the disease as a whole and can characterize all tumour locations. This type of parameters is well suited to some cancers, notably lymphomas and probably metastatic solid cancers, as shown by the predictive value of known parameters like TMTV [5], TVSR [12] or Dmax [20].…”
Section: Discussionmentioning
confidence: 99%
“…The twelve following parameters were determined on the baseline PET/CT by an in-house software called “Oncometer3D”, with a graphical representation of the parameters visible in Fig. 3 : (1) SUVmax, the highest maximal standardized uptake value (SUV) measured in all tumours, (2) SUVmean, the mean value of SUV measured in all tumours, (3) total metabolic tumour volume (TMTV) obtained by summing the metabolic volumes of all the nodal and extra-nodal lesions, (4) total lesion glycolysis (TLG) calculated as the product of the MTV and the SUVmean (TLG = TMTV × SUVmean), (5) total metabolic tumour surface (TMTS) obtained by summing the metabolic surfaces of all tumours [ 12 ], (6) tumour volume surface ratio (TVSR) corresponding to the ratio of the TMTV and the TMTS [ 12 ], (7) volume of the bounding box including the tumours (TumBB) corresponding to the volume of tumour dispersion, (8) the maximal tumour distance (Dmax) corresponding to the distance between the two lesions that were the furthest apart [ 20 ], (9) the number of regions of interest (nROI) corresponding to the number of unique tumour on the whole examination, (10) iterative erosion (itErosion) corresponding to the number of erosions [ 30 ] required to remove tumours from the images, (11) the median distance between the centroid of the tumours and the periphery (medPCD), (12) the median edge distance (medEdgeD) corresponding to the median distance between the opposite edges of the tumours.
Figure 3 Representation of the twelve different PET parameters measured by the software Oncometer3D and analysing burden, activity, dispersion, fragmentation and massiveness of the lymphoma.
…”
Section: Methodsmentioning
confidence: 99%